Personality Typology of Thahir and Syaban in Short Story “Nikosia” By Saadi Youssef: A Literary Psychology Study - Mufaddal; Nur Chalis; Anshar Zulhelmi (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2026)
The purpose of this study is to examine the personality types of Thahir and Syaban characters in the short story Nikosia by Saadi Youssef. This research applies a qualitative descriptive method, utilizing the literary psychology approach of Hippocrates-Galenus personality theory. This study relies on written data derived from Saadi Youssef’s short story Nikosia, which illustrates the alignment of the main character’s personality with the Hippocrates-Galenus perspective. Data collection techniques employed in this study include reading and note-taking, library research, close reading, and manual coding. The data were processed using analysis techniques that involve identification, in-depth analysis, and drawing conclusions. The results of this study reveal that the four personality types defined by Hippocrates sanguine, choleric, melancholic, and phlegmatic are evident in the characters of the short story Nikosia by Saadi Youssef. The author hopes that this research can contribute to future studies regarding the Hippocrates-Galenus literary psychology theory.